The Impact of Bank’s Ownership Concentration on Indonesia Banking System Stability - Jonathan Aldo Jaya,Telisa Aulia Falianty (International Conference on Industrial Revolution for Polytechnic Education, 2020)
This study aims to examine the role of banks ownership concentration on banking system stability in Indonesia. The bank ownership concentration is divided into 3 concentration levels, i.e. banks are concentrated in share of ownership: (1) <20%; (2) 20-50%; (3) >50%. While the banking system stability is measured by ZScore. The data are individual of 115 banks registered to Otoritas Jasa Keuangan from 2008 to 2017. By using panel data regression, it was found that banks with owners concentration on level 3 would make the banking system stable. However, banks with owners concentrated in levels 1 and 2 will make the financial system unstable.